Psychological and immunological associations with movement-evoked low back pain among older adults - Riley Kahan; Arthur Woznowski-Vu; Janet L. Huebner; Carl F. Pieper; Adam P. Goode; Steven Z. George; Timothy H. Wideman; Virginia Byers Kraus; Cathleen Colón-Emeric; Corey B. Simon (PAIN Reports)
Abstract. Introduction:. Low back pain (LBP) is a leading global factor in disability among older adults. Movement-evoked pain (MEP) is potentially an important mediator in the disability pathway but is predominantly tested in the laboratory. Objectives:. We aimed to explore MEP in the natural environment (“daily” MEP) and its correlation with laboratory MEP, along with potential psychological and immunological influences. Method:. Thirty-five older adults with persistent LBP attended a single laboratory session. Pain catastrophizing, pain-related fear of movement, and pain self-efficacy were measured by questionnaire. Resting inflammation and inflammatory reactivity to painful movement were evaluated using serum interleukin-6, tissue necrosis factor alpha, and C-reactive protein (CRP). Laboratory MEP was defined by aggregate pain intensity with a movement provocation test. Daily MEP was measured for the next 7 days using ecological momentary assessment. Results:. Laboratory MEP was strongly correlated with daily MEP (ρ = 0.780, P = <0.001). C-reactive protein (Hedges [g] = 0.266) and interleukin-6 (g = 0.433) demonstrated small to moderate reactivity to painful movement. After controlling for age and multimorbidity, pain catastrophizing and pain self-efficacy explained 24% to 37% variance in laboratory and daily MEP. Resting inflammatory markers were not associated with MEP; however, C-reactive protein reactivity to painful movement explained 19% to 25% variance in laboratory and daily MEP. Conclusion:. Preliminary indication is that laboratory and daily MEP may be proxy measures for one another, and that MEP is influenced by psychological and immunological factors. Future studies will aim to (1) validate findings among older adults with persistent LBP and (2) for clinical phenotyping, clarify complex relationships among psychological and immunological factors with disability pathway components like MEP.